A Critique of Digital Feminism from an Islamic Moderation Perspective: A Study of Gender Representation in Social Media - Ady Avnan; Fathorrahaman (Penerbit Hellow Pustaka, 2025)
The rise of social media as a digital expression space has created significant opportunities for the dissemination of feminist discourse, particularly through digital feminism. This movement leverages platforms like TikTok and Instagram to advocate for gender equality, dismantle patriarchal norms, and promote women's rights. However, in predominantly Muslim societies such as Indonesia, digital feminism often clashes with Islamic values, especially when addressing sensitive issues like the hijab, polygamy, and women’s domestic roles. This study aims to examine the narratives of digital feminism from the perspective of Islamic moderation (wasathiyah), in order to find a middle ground between gender justice and Islamic principles. Using a qualitative approach and critical discourse analysis of social media content and Muslim audience responses, the study finds that digital feminist narratives tend to emphasize absolute freedom and frequently portray Islam as inherently patriarchal. Conversely, the moderate Islamic approach highlights justice, balance, and partnership between men and women. The findings suggest that wasathiyah offers a constructive framework for dialogue between Islamic values and gender equality struggles in the digital space. Therefore, there is a need for educational and alternative narratives that integrate sharia values with principles of social justice, so that gender discourse on social media can become more contextual, balanced, and unbiased.